Challenges and opportunities to prevent transfusion errors: a Qualitative Evaluation for Safer Transfusion (QUEST). - Heddle, N; Fung, M; Hervig, T; Szczepiorkowski, Z; Torretta, L; Arnold, E; Lane, S; Murphy, M; BEST Collaborative (2012)
BACKGROUND: One of the most frequent causes of transfusion-associated morbidity or mortality is the transfusion of the wrong blood to the wrong patient. This problem persists in spite of the incorporation of numerous procedures into the pretransfusion checking process in an effort to improve patient safety. A qualitative study was undertaken to understand this process from the perspective of those who administer blood products and to identify concerns and suggestions to improve safety. STUDY DESIGN AND METHODS: Twelve focus group discussions and seven individual interviews were conducted at six hospitals in five countries (n = 72 individuals). Health care professionals from a variety of clinical areas participated. Data analysis identified common themes using the constant comparison method. RESULTS: Five major themes emerged from the analysis: the pretransfusion checking process, training, policy, error, and monitoring. Findings include the following: staff were aware and appreciative of the seriousness of errors and were receptive to continuous monitoring, the focus was on checking the bag label with the paperwork rather than the bag label with the patient at the bedside, training methods varied with most perceived to have minimal effectiveness, and access to policies was challenging and keeping up to date was difficult. Other factors that could contribute to errors included high volume of workload distractions and interruptions and familiarity or lack of familiarity with patients. CONCLUSIONS: Multiple factors can contribute to errors during the pretransfusion checking limiting the effectiveness of any individual intervention designed to improve safety. Areas of further research to improve safety of blood administration were identified.